2006
DOI: 10.5395/jkacd.2006.31.1.058
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of relative reliability on biaxial and three point flexural strength testing methods of light curing composite resin

Abstract: The possibility of applying a bi-axial flexure strength test on composite resin was examined using three point and bi-axial flexure strength tests to measure the strength of the light-cured resin and to compare the relative reliability using the Weibull modulus.The materials used in this study were light-curing restorative materials, MICRONEW TM , RENEW � (Bisco, Schaumburg, USA). The bi-axial flexure strength measurements used the piston-on-3-ball test according to the regulations of the International Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Several factors influence the measurement of flexural strength such as the testing method, specimen dimensions, testing environment, polishing procedures, stress rates, and stress area. 39,40 Other than polishing procedures with D+Z and OptraFine systems, no other differences were found between the two groups with respect to the abovementioned factors. Finer diamond particles of the polishing paste of the OptraFine system may result in shallower scratches and fewer surface flaws, cracks, porosities, and irregularities.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several factors influence the measurement of flexural strength such as the testing method, specimen dimensions, testing environment, polishing procedures, stress rates, and stress area. 39,40 Other than polishing procedures with D+Z and OptraFine systems, no other differences were found between the two groups with respect to the abovementioned factors. Finer diamond particles of the polishing paste of the OptraFine system may result in shallower scratches and fewer surface flaws, cracks, porosities, and irregularities.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the flexural strength of the grinding‐D+Z group was measured to be significantly lower than that of grinding‐OptraFine group. Several factors influence the measurement of flexural strength such as the testing method, specimen dimensions, testing environment, polishing procedures, stress rates, and stress area . Other than polishing procedures with D+Z and OptraFine systems, no other differences were found between the two groups with respect to the abovementioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our data obtained from IPS e.max CAD were relatively higher than the values claimed by the manufacturers. It has been reported that the biaxial flexure test tends to yield higher values than the 3-point flexure test 10. Our data were close to the results reported by Buso et al and Lin et al [mean flexural strength (SD) of 416.1 (50.1) MPa and 365.1 (46.0) MPa], which had been obtained from specimens of a similar size and shape to ours and by a similar method 3,11.…”
Section: Discussionmentioning
confidence: 99%
“…Biaxial flexural strength test does not show edge failure and the effect of crack direction is minimal, and therefore, is considered more accurate than uniaxial flexural strength. 27,28 Thus, the flexural strength was measured using biaxial test and approximately 650 to 750 MPa was measured in groups without additional firing. The result was similar to the flexural strength of another pre-shaded 5Y-ZP reported by Kwon et al 14 Although the 5Y-ZP showed a lower flexural strength than that of 3Y-TZP due to the lack of transformation toughening, it yielded higher flexural strength than lithium disilicate.…”
Section: Discussionmentioning
confidence: 99%